فاعلية دراسة "مساق تكنولوجيا المواد النانوية" في اكتساب أساسيات النانوتكنولوجي والاتجاه نحوها - ملكاوي، آمال رضا (جامعة اليرموك - عمادة البحث العلمي, 2017)
هدفت هذه الدراسة إلى تقصي فاعلية دراسة مساق "تكنولوجيا المواد النانوية" في اكتساب أساسيات النانوتكنولوجي والاتجاهات نحوها لدى عينة من طلبة هندسة المواد في جامعة البلقاء التطبيقية. تكونت العينة من (24) طالبا وطالبة من الطلبة المسجلين للمساق في الفصل الأول من العام الدراسي (2015-2016). ولقياس درجة اكتساب الطلبة لأساسيات النانوتكنولوجي, تم بناء اختبار تكون من (35) فقرة، ولقياس الاتجاهات نحوها تم بناء مقياس تكون من (29) فقرة. تم تطبيق اختبار المعرفة ومقياس الاتجاهات على عينة الدراسة قبليا. ثم درست العينة محتوى مساق تكنولوجيا المواد النانوية لمدة (14) أسبوعاً بواقع (3) ساعات أسبوعياً، ثم تم تطبيق الاختبار ومقياس الاتجاهات تطبيقاً بعدياً. وأظهرت النتائج وجود أثر دالّ إحصائيا لدراسة المساق في اكتساب الطلبة لأساسيات النانوتكنولوجي، وتحسين اتجاهاتهم نحوها. وكشفت النتائج كذلك عن علاقة ارتباطية دالّة موجبة بين مستوى معرفة الطلبة بأساسيات النانوتكنولوجي واتجاهاتهم نحوها.
This study aimed to identify the effectiveness of studying an introductory course in "Technology of Nanomaterials" on the acquisition of fundamental knowledge and attitudes towards nanotechnology among students of engineering materials at Balqa Applied University in Jordan. The sample consisted of (24) students enrolled in the course during the first semester of the academic year 2015-2016. To measure the students acquisition of fundamental knowledge of nanotechnology, a test consisted of (35) items was applied, and to determine students' attitudes, a questionnaire consisted of (29) items was applied to the same sample. The sample studied a course in Technology of Nanomaterials for (14) weeks; (3) hours a week. Then the two instruments were admistered as post tests. The results showed statistically significant differences in acquiring knowledge of and attitudes towards nanotechnology. The results also revealed a positive correlation between them.This study aimed to identify the effectiveness of studying an introductory course in "Technology of Nanomaterials" on the acquisition of fundamental knowledge and attitudes towards nanotechnology among students of engineering materials at Balqa Applied University in Jordan. The sample consisted of (24) students enrolled in the course during the first semester of the academic year 2015-2016. To measure the students acquisition of fundamental knowledge of nanotechnology, a test consisted of (35) items was applied, and to determine students' attitudes, a questionnaire consisted of (29) items was applied to the same sample. The sample studied a course in Technology of Nanomaterials for (14) weeks; (3) hours a week. Then the two instruments were admistered as post tests. The results showed statistically significant differences in acquiring knowledge of and attitudes towards nanotechnology. The results also revealed a positive correlation between them.
Keywords: التعليم الجامعي -- تكنولوجيا المعلومات -- النانوتكنولوجي -- جامعة البلقاء التطبيقية